Feasibility and safety of intrathecal treatment with nusinersen in adult patients with spinal muscular atrophy. (October 2018) - Stolte, Benjamin; Totzeck, Andreas; Kizina, Kathrin; Bolz, Saskia; Pietruck, Lena; Mönninghoff, Christoph; Guberina, Nika; Oldenburg, Denise; Forsting, Michael; Kleinschnitz, Christoph; Hagenacker, Tim
Background: Nusinersen is an intrathecally administered antisense oligonucleotide (ASO) and the first approved drug for the treatment of spinal muscular atrophy (SMA). However, progressive neuromyopathic scoliosis and the presence of spondylodesis can impede lumbar punctures in SMA patients. Our aim was to assess the feasibility and safety of the treatment in adults with SMA. Methods: For the intrathecal administration of nusinersen, we performed conventional, fluoroscopy-assisted and computer tomography (CT)-guided lumbar punctures in adult patients with type 2 and type 3 SMA. We documented any reported adverse events and performed blood tests. Results: We treated a total of 28 adult SMA patients (9 patients with SMA type 2 and 19 patients with SMA type 3) aged between 18–61 years with nusinersen. The mean Revised Upper Limb Module (RULM) score at baseline in SMA type 2 and SMA type 3 patients was 9.9 ± 4.6 and 29.5 ± 8.5, respectively. The mean Hammersmith Functional Motor Scale Expanded (HFMSE) score at baseline was 3.1 ± 2.5 and 31.2 ± 18.1, respectively. Half of the SMA type 3 patients were ambulatory at treatment onset. In total, we performed 122 lumbar punctures with 120 successful intrathecal administrations of nusinersen. Lumbar punctures were well tolerated, and no serious adverse events occurred. Conclusions: Our data demonstrate the feasibility and tolerability of intrathecal treatment with nusinersen in adults with SMA type 2 and type 3. However, treatment can be medically and logistically challenging, particularly in patients with SMA type 2 and in patients with spondylodesis.